Digitalization and the Changing Landscape of Tax Compliance (Challenges and Opportunities) - Hidayat, Muhammad; Defitri, Siska Yulia (Accounting Studies and Tax Journal (COUNT), 2024)
This research discusses the impact of digital transformation on tax compliance by conducting a systematic literature review. Through appropriate keyword selection, relevant articles were identified from leading academic databases such as Scopus, IEEE Xplore, ScienceDirect, JSTOR, and Google Scholar. Analysis of the literature reveals technological complexity, increasing administrative efficiency, and emerging regulatory challenges as the main categories. Apart from that, information disclosure, the use of new technology in tax risk analysis, and changes in the paradigm of taxpayer involvement are also the main focus. In conclusion, digital transformation not only creates new challenges in tax compliance, but also brings opportunities to increase the effectiveness and openness of the tax system.